Dialect Identification on Kangean Island and Madurese Island: Dialectology Study - Mochammad Minladun Hakim; Agus Sariono; Asrumi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2022)
Madurese language is one of the regional languages ​​in Indonesia which has various dialect variations, namely Bangkalan dialect, Pamekasan, Sumenep, and Kangean. However, the Kangean dialect is considered a separate language by the Madurese in general. This study aims to reveal and identify the isolect status of the language used on Kangean Island and Madurese Island. This study uses the dialectometric method. Data was collected using a list of 845 questions taken from 3 informants at each observation point (OP). Data analysis used the dialectometric method with the formula proposed by Guiter. The results of this study showed 4 categories, namely, no difference (<20%), different speech (21%-30%), different sub-dialect (31%-50%), and different dialect (51%-80%). This study shows there are 2 OP with no difference in status, 2 OP with speech differences, 7 OP in subdialect on Kangean Island. And if all OPs on Kangean Island were compared with OPs on Madurese Island, each has the status of a dialect.